The Effectivity of Mind Mapping as Preparation Media for Selection of Advanced Studies to Higher Education - Taty Fauzi; Valeri Adventa Tiffany Nathani Ela (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2022)
Mind mapping is a way to record obtained information by mapping the mind which done creatively to make it more effective and easier to absorb by the brain. The purpose of this study is to determine the effectiveness of mind mapping media as a preparation for choosing a study to higher education. Current research is a quantitative pre-experimental research with a one group pre-test post-test design. The mind mapping used is a syllabus, a type of mind mapping that can provide an overview of what students know and learn. Media